Development of a functional biodegradable composite with antibacterial properties. (19th September 2018) - Tong, Shi Yun; Lim, Poon Nian; Wang, Kaiying; Thian, Eng San
ABSTRACT: Creating antimicrobial property in biomaterials has always been generating interest in food packaging and biomedical applications to combat pathogenic microorganisms. Poly-ɛ-caprolactone (PCL) is a biodegradable polymer which has been investigated extensively due to its ease of processability. In this study, natural antibacterial substances alginic acid (ALG) particles and grapefruit seed extract (GFSE) were added into PCL matrix using mechanical blending processes to obtain a novel antibacterial and biodegradable composite material, which can be used for various applications like food packaging, tissue engineering and drug delivery. The blend was then compressed into film via compression moulding. The film surfaces were smooth and homogeneous. Results showed changes in crystallinity after the addition of GFSE. Fabricated composite blend was effective against Pseudomonas aeruginosa ( P. aeruginosa ). The improved antimicrobial activity of the blend indicated the potential for combating infections.